A comparison of physiological responses to rowing on friction-loaded and air-braked ergometers - Mahony, N.; Donne, B.; O'Brien, M. (Journal of Sports Sciences, 1999)
The physiological responses of 10 trained rowers to a progressive incremental rowing protocol to exhaustion were investigated on Gjessing, Rowperfect fixed-mechanism and Rowperfect free-mechanism rowing ergometers. Heart rate, oxygen uptake (VO2), ventilation (VE) and blood lactate were determined at matched power values for each ergometer. The mean power and heart rate at the lactate anaerobic threshold were determined by graphical interpolation of data for each ergometer. Analysis of variance and linear regression showed differing responses at matched power and an approximate 40-50 W difference in power at the lactate anaerobic threshold when comparing the friction-loaded Gjessing with the air-braked Rowperfect fixed and Rowperfect free ergometers (P<0.01). No significant differences were noted when comparing the air-braked Rowperfect fixed and Rowperfect free ergometers. However, comparisons of VO2, VE and blood lactate at given heart rates and of heart rate at the lactate anaerobic threshold showed no significant differences between ergometers. Our results indicate similar physiological profiles for all ergometers tested when compared at equivalent heart rates, but differences when compared at matched power. A direct comparison of the data from Gjessing (friction-loaded) with Rowperfect fixed and Rowperfect free (air-braked) ergometers would therefore require a correction factor for inter-ergometer variation in displayed power data.